The relationship between oxygen consumption and body acceleration in a range of species - Halsey, L. G. (2009)
The ability to measure the energy expenditure of free-ranging animals is of great importance but the techniques available each have their limitations. Recently, as an alternative to more established techniques, an integrated measure of body acceleration termed overall dynamic body acceleration (ODBA) has been used as a calibrated proxy for rate of oxygen consumption (V̇O2) and hence metabolic rate. The present study tested the potential of this technique, firstly by expanding the range of species for which the V̇O2-ODBA relationship has been defined and secondly by undertaking a validation exercise to explore the accuracy of predictions made using ODBA. V̇O2-ODBA relationships during terrestrial locomotion were established for several bipedal and quadrupedal endotherms and compiled with similar relationships previously determined in other species. A model incorporating all of these species showed that ODBA is an excellent predictor of V̇O2 but there is variation in the V̇O2-ODBA relationship between species, and further variation within some species. Including measurements such as body mass and structural size in prediction equations might further improve the predictive power of the 'ODBA technique' and eliminate species-specific differences. In the validation exercise, estimate errors were calculated for the species-specific predictive equations. The use of ODBA to estimate V̇O2 was valid across all species examined and may show a greater potential for estimating energy expenditure for individual animals than other techniques.